Nation Building and Intelligence Reforms Debacle in Transitional Democracies: A Review of Post-Colonial Hangovers in Nigeria - Nte, Ngboawaji Daniel (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This paper is an elucidation of the intricate challenges of nation building and intelligence reforms in transitional democracies where there are inherent contradictions of the imperatives of democratic ethos vis a vis intelligence reforms to create a credible balance of modern societies, with a specific focus on Nigeria. It is the position of this paper that the country's post-colonial hangovers have greatly impacted the national capacity to establish and nurture a dynamic template for the establishment of a robust and effective intelligence architecture. The consequence therefrom is a highly ineffective national security and democratic consolidation. The methodological thrust of the paper is a historical review of the political economic context of Nigeria's intelligence apparatus, the challenges of reforming it, and the consequential implications for nation building gathered logically from secondary sources. It concludes by highlighting the need for a comprehensive overhaul of the intelligence sector, anchored on democratic values and the rule of law.